Risk of transmission of COVID-19 from healthcare workers returning to work after a 5-day isolation, and kinetics of shedding of viable SARS-CoV-2 variant B.1.1.529 (Omicron). (January 2023) - Jung, J.; Kang, S.W.; Lee, S.; Park, H.; Kim, J.Y.; Kim, S.-K.; Park, S.; Lim, Y.-J.; Kim, E.O.; Lim, S.Y.; Chang, E.; Bae, S.; et al.
Summary: Background: There have been limited data on the risk of onward transmission from individuals with Omicron variant infections who return to work after a 5-day isolation. Aim: To evaluate the risk of transmission from healthcare workers (HCWs) with Omicron variant who returned to work after a 5-day isolation and the viable-virus shedding kinetics. Methods: This investigation was performed in a tertiary care hospital, Seoul, South Korea. In a secondary transmission study, we retrospectively reviewed the data of HCWs confirmed as COVID-19 from March 14 th to April 3 rd, 2022 in units with five or more COVID-19-infected HCWs per week. In the viral shedding kinetics study, HCWs with Omicron variant infection who agreed with daily saliva sampling were enrolled between February and March, 2022. Findings: Of the 248 HCWs who were diagnosed with COVID-19 within 5 days of the return of an infected HCW, 18 (7%) had contact with the returned HCW within 1–5 days after their return. Of these, nine (4%) had an epidemiologic link other than with the returning HCW, and nine (4%) had contact with the returning HCW, without any other epidemiologic link. In the study of the kinetics of virus shedding ( N = 32), the median time from symptom onset to negative conversion of viable virus was four days (95% confidence interval: 3–5). Conclusion: Our data suggest that the residual risk of virus transmission after 5 days of isolation following diagnosis or symptom onset is low.